The redistribution and insurance value of welfare reform - Jonathan Shaw (Institute for Fiscal Studies (IFS), 2014)
Relatively little is known about the roles that taxes and transfers play in redistributing resources and providing insurance across individuals and across the lifecycle. We embed these alternative roles in a lifecycle model, allowing us to demonstrate what the tax and transfer system achieves from a lifecycle perspective and why it is valuable. We undertake a five-way de-composition of net transfers into a giveaway term and terms corresponding to between- and within-individual redistribution and between- and within-individual insurance. These components are distinguished from perspective of the start of working life, and we consider both the magnitude of net transfers involved and the associated welfare values. Our focus is on females and we also highlight how behavioural responses affect the results. Analysis is conducted for the 2015 UK tax and transfer system relative to a at-rate baseline, showing what value is provided by the complex tax and welfare entitlement rules in a modern economy. We also consider what is achieved by two important UK bene t reforms the working families' tax credit (WFTC) reform of 1999 and the universal credit (UC) reform that began in 2013. Our main conclusions are that insurance against wage and family composition shocks is substantial and highly valued by individuals. Within-individual redistribution (i.e. across periods of life) is generally of little value even in the presence of strict borrowing constraints. Behavioural responses tend to increase the size of reform giveaways at the expense of the other components.
Keywords: 330; tax; insurance; redistribution